PENGARUH JUMLAH ISIAN PROPELAN TERHADAP KECEPATAN PROYEKTIL MUNISI KALIBER 40X46 MM NON-LETHAL - Sanjiwani, Yudistira; Pratikto, Pratikto; Irawan, Yudy Surya (Jurnal Rekayasa Mesin, 2024)
Many kinds of non-lethal ammunitions are developed in the last fourty years. The 40x46 mm Non-lethal ammunition is one of several ammunitions ready to be used in riot control. This type of ammunition can be used to subdue the target by implementing impact force. When developing non-lethal ammunition, it should be considered that the ammunition has adequate projectile velocity to ensure that the impact will produce sufficient pain to immobilize the target without risk of permanent injury. Projectile velocity is affected by the propellant weight and projectile weight. Therefore, a study to understand the effect of propellant charge weight on projectile velocity was done experimentally. This experiment was done by preparing several variations of propellant charge weight which were 0.150 gram, 0.200 gram, 0.250 gram, 0.300 gram and 0.350 gram. The desired output of this study is to obtain the correct amount of propellant charge weight to produce projectile velocity in accordance with the 40x46 mm Non-Lethal ammunition specification. The conclusion of this study is that Variation C ammunition with propellant charge weight of 0.250 gram is the closest variation to achieve nominal projectile velocity of 75 m/s. The exact range of propellant charge weight that can be used as production guidelines in order to comply with the product specification is between 0,228-0,280 grams APS350.